STIMULATION GROWTH AND YIELD OF POTATO BY BUTTONWOOD PRUNNING RESIDUES AND SPRAYING SEVERAL MICRONUTRIENTS - & Al-Amri, Al-Dulaimi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to estimate the influence of Conocarpus erectus L. residues, and some micronutrients on growth and production of potato. This research was conducted at one of the fields of the College of Agricultural Engineering Sciences - University of Baghdad. The experiment was implemented using factorial arrangement (4X3X3) within randomized complete block design with three replicates. Conocarpus fertilizer was represented the first factor with three levels (7.5, 15, 30 ton.ha-1), which symbolized (C2, C3, C4). Mineral fertilizer as recommended dose as a control, which symbolized (C1). The second factor was foliar spraying with three levels of iron (0, 100, 200 mg.L-1), which symbolized (F0, F1, F2). The third factor is foliar spraying with three levels of boron (0, 50, 100 mg.L-1), which symbolized (B0, B1, B2). Results revealed that the treatments C1 and C3 produced significant results in most of studied traits such as, Leaves number (71.74, 82.26 leaves plant-1), leaves chlorophyll content (223.30, 174.11 mg 100g wet weight) and total yield (84.24, 51.98 ton h-1) for both seasons respectively, while C1 and C4 produced the most significant protein percent reached (7.53, 7.71%) respectively. The foliar application of Fe at F2 produced the highest results in leaves number (70.47, 80.18 leaves plant-1), protein percent (7.40, 7.55%) for both seasons respectively, Also the foliar application of Boron at B1 and B2 produced a significant results  in leaves number (68.58, 78.71 leaves plant-1), total yield (48.47, 76.00 ton h-1), and protein percent (7.43, 7.49%) for both seasons respectively. Furthermore, the third order interaction at the treatment C3F2B2 produced the highest protein percent (7.78%) in spring season only.